Modeling and Measurements of Novel Monolithic Filters - Aly H. Aly; Badawy El-Sharawy; Adalbert Beyer (Active and Passive Electronic Components)
This paper presents novel multilayer tuneable high Q-filters based on hairpin resonators including ferroelectric materials. This configuration allows the miniaturization of these filters to a size that makes them suitable for chip and package integration and narrow-band applications. The main focus was miniaturizing filters with coupled loops using multilayer dielectric substrates. A further goal was to increase the quality factor of these distributed filters by embedding high dielectric materials in a multilayer high- and low-k (dielectric constant) substrate that is supported by LTCC technology. An improved W-shape bandpass filter was proposed with a wide stopband and approximately 5% bandwidth.